Object-oriented test pattern generator and logic simulator for combinational circuits - 486773 Ooi, Chia Yee (Skudai : Universiti Teknologi Malaysia, 2003)
Thesis (Master of Engineering (Electrical)) - Universiti Teknologi Malaysia, 2003